2019
DOI: 10.1007/s00251-019-01112-1
|View full text |Cite|
|
Sign up to set email alerts
|

HLA-F*01:01 presents peptides with N-terminal flexibility and a preferred length of 16 residues

Abstract: HLA-F belongs to the non-classical HLA-Ib molecules with a marginal polymorphic nature and tissue-restricted distribution. HLA-F is a ligand of the NK cell receptor KIR3DS1, whose activation initiates an antiviral downstream immune response and lead to delayed disease progression of HIV-1. During the time course of HIV infection, the expression of HLA-F is upregulated while its interaction with KIR3DS1 is diminished. Understanding HLA-F peptide selection and presentation is essential to a comprehensive underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…Recently, it has been shown that the polymorphism of HLA-F allelic variants does not influence peptide features of presented peptides [8]. The pHLA structure of HLA-F differs from the classical pHLA structure [6,7]. The binding of long peptides that protrude out at the N terminal side of the peptide-binding region leads to the formation of a very flexible, accessible surface of HLA-F. For HLA-E, it could be demonstrated that peptides dictate the interaction partner; depending on the presented peptide, HLA-E constitutes a ligand for inhibitory NKG2A/CD94 receptor or activating NKG2C/CD94 receptor on NK cells [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the polymorphism of HLA-F allelic variants does not influence peptide features of presented peptides [8]. The pHLA structure of HLA-F differs from the classical pHLA structure [6,7]. The binding of long peptides that protrude out at the N terminal side of the peptide-binding region leads to the formation of a very flexible, accessible surface of HLA-F. For HLA-E, it could be demonstrated that peptides dictate the interaction partner; depending on the presented peptide, HLA-E constitutes a ligand for inhibitory NKG2A/CD94 receptor or activating NKG2C/CD94 receptor on NK cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been assumed that HLA-F is entirely unable to present peptides [3], implying HLA-F to display an invariant surface for its cognate receptor. Recently, it has been demonstrated that HLA-F is able to assemble with β2m and to bind and present peptides like classical HLA-I molecules [6,7]. Of note, peptides selected and presented by HLA-F exhibit unusual length [6,8]; further analysis revealed that the peptides are exclusively C terminal anchored; the unique structure of the HLA-F peptide-binding region (PBR) impedes the classical pocket A and pocket B engagement and enables the binding of these long peptides [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…For proteome analysis, cells were lysed in RIPA buffer as described by Ho et al [64]. Cell suspension was thoroughly vortex and incubated on ice for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Initially it was assumed that HLA-F is entirely unable to present peptides. Yet, it could be demonstrated recently that HLA-F is able to select, bind and present peptides [3,4]; trimeric complexes of HLA-F heavy chain, β2m and peptide could be isolated following their assembly within the cells. Those HLA-F bound peptides are of unusual length and the binding mode to the peptide binding region reveals an open end conformation without the classical pocket A or pocket B engagement; this observation explains the existence of HLA-F OCs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their marginal polymorphic nature and proposed immunological invariability, most HLA-Ib allelic variants differ substantially in their peptide profiles [14,15,16]; this variability results in differential immune responses [17,18]. All investigations to elucidate the function of HLA-F concentrate on the most frequent allelic variant HLA-F*01:01 (Table 1) [3,4,19,20,21]. A recent study on the haplotype lineages of HLA-F describes the relation between haplotypes and RNA expression levels [22]; moreover, recently a significant association of HLA-F polymorphism on genomic level with chronic HBV infection has been suggested [23].…”
Section: Introductionmentioning
confidence: 99%